TEACHING NARRATIVE READING TEXT BY USING 3H (HERE, HIDDEN, IN MY HEAD) STRATEGY TO THE TENTH GRADE STUDENTS OF SENIOR HIGH SCHOOL OF ARINDA PALEMBANG - Resti Riyani (Edukasi, 2016)
In this study, the writer was interested to use 3H (Here, Hidden, in my Head) strategy in teaching reading specifically in teaching narrative reading text. The objective of this study was to find out whether or not there is significant different in students’ reading achievement between those who are taught by using 3H (Here, Hidden, in my Head) strategy and GTM (grammar translation method) to the tenth grade students of senior high school of Arinda Palembang in the academic year of 2014/2015. The population of the study were 97 students from 3 classes. The sample of the study was taken from convenience sampling. The writer selected X.1 as the control group and X.2 as the experimental group. It consisted of 62 students, 30 students for control group and 32 students for experimental group. In this study, the writer used quasi-experimental design. The instrument used in collecting the data was written test, and interview. The test was administered twice, as the pretest and posttest for both control and experimental group. The result of the test were analyzed by using SPSS 16. The result showed that the p-output was 0.009 and the t-value was 2.736. Since the p-output was lower than 0.05 and the t-value was higher than t-value 2.000. It means that, the null hypothesis (Ho) was rejected and alternative hypothesis (Ha) was accepted. It can be stated that there was a significant difference in students’ reading achievement taught by using 3H (Here, Hidden, in my Head) strategy and GTM (grammar translation method) to the tenth grade students of senior high school of Arinda Palembang in the academic year of 2014/2015.